USER EXPERIENCE OF E-PPGBM APPLICATION ON USERS OF PUBLIC HEALTH CENTER IN KUTACANE CITY USING THE UTAUT METHOD - Ekanugraha, Edwin; Andrian , Nasrun; Prasandy , Teguh (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2024)
In order to support the National Stunting Reduction Movement, the Ministry of Health of the Republic of Indonesian creates an application to record and report the nutritional status of the community, namely e-PPGBM or Electronic Community-Based Nutrition Recording and Reporting. Furthermore, in an effort to improve the services which are provided by users, this study was conducted by measuring user acceptance and improving service design so that it will help improve e-PPGBM functions, user experience, and ultimately generate value by helping nutritionists, health workers and policy makers in their work. The user acceptance method used in this study was the UTAUT model. The samples in this study were 35 respondents. Moreover, data collection was conducted by distributing questionnaires via Google Form and the results would be analyzed by using SmartPLS. Based on the results of data processing on SmartPLS, the f-square value on the relationship between effort expectancy variables and behavioral intention has a value of 0.118 which means that the UX improvement will be conducted. The suggestion for improving the new design are focused on adding features to the dashboard that is button as a new data input function and graphics as a function of displaying data from recording and reporting results through the e-PPGBM application.